Social assessment of the impact of oil exploitation on lives of inhabitants and the environment - Rychlicki, Stanisław; Kosowski, Piotr; Wartak, Joanna; Solecki, Marek (My University, 2016)
This article presents the results of surveys carried out in the framework of the MUSE project in order to gain knowledge and obtain assessment of the impact of oil exploitation on the lives of the inhabitants of certain regions and on the environment. The survey was conducted in Krosno, Jedlicz and Rymanów (SE Poland). In this area, since the nineteenth century, there are o lot of crude oil mines and many local people are employed at its exploitation. Current condition of the environment and the negative effects of pollution and its causes were assessed by the local community. Within the framework of the conducted study, particular attention was paid to assessing the impact of oil exploitation on the environment and human health. Respondents also pointed to environmental elements that have gone under the greatest transformation in connection with the exploitation of crude oil.
AGH Drilling, Oil, Gas
Keywords: oil exploitation; survey; social assessment; social acceptance